The Impact of Teacher’s Involvement in MGMP on the Teachers’ Performance - Sumiyani, Sumiyani (PPSDP International Journal of Education, 2023)
This research paper examines the impact of teacher involvement in the MGMP (subject-subject teacher consultation) program on teacher performance in Indonesian schools. The study investigates the level of engagement of Indonesian instructors in the MGMP and explores how their participation affects their effectiveness as educators. Furthermore, the paper examines the relationship between teacher participation in the MGMP and student achievement, emphasizing the influence of the program on student learning outcomes. The research methodology employed a qualitative approach, using interviews, observations, and document analysis to gather data from teachers in Tangerang City. The findings highlight the importance of active participation in the MGMP, as it enables teachers to collaborate on various aspects related to improving teaching practices, including the development and use of teaching programs, production and utilization of teaching aids, adoption of teaching methods, assessment of student learning processes and outcomes, utilization of the learning environment, classroom management, and other learning-related activities. It is hoped that this research will encourage teachers to actively contribute to resolving school-related issues and promote teacher professionalism through their engagement in the MGMP, especially those pertaining to teacher professionalism.